The role of organizational commitments in mediating the effect of work motivation and job satisfaction towards turnover intention on nurses private hospital - Astiti, Made Widya; Surya, Ida Bagus Ketut (International research journal of management, IT and social sciences, 2020)
This study aims to determine the role of organizational commitment in mediating the effect of work motivation and job satisfaction on turnover intention of nurses at private hospitals in South Kuta. The number of samples used was 82 nurses using saturated sampling technique or census methods and collecting data using a questionnaire that uses a Likert scale. The data analysis technique was performed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, and the VAF test to test the role of mediation. The results show that there is a negative and significant influence of organizational commitment, work motivation and job satisfaction on turnover intention. There is a positive and significant effect of job satisfaction and work motivation on organizational commitment, as well as the role of organizational commitment as a partial mediator between work motivation and job satisfaction on turnover intention which has a negative and significant effect. The findings in this study imply that companies are required to pay more attention to appropriate compensation and to reward employees who are loyal to the company and pay attention to the working conditions of their employees so that employees will remain in the company.